Ubuntu translanguaging as a systematic approach to language teaching in multilingual classrooms in South Africa - Sefotho, Malephole Philomena M. (Journal for Language Teaching, 2022)
The Language in Education Policy recognises the linguistically super-diverse nature of learners in South African schools and provides allowance to use more than one language in teaching and learning within the framework of promoting multilingualism. This policy adopted an additive approach and encouraged school governing bodies to establish how they will promote multilingualism through the use of more than one language. However, it seems there is lack of systematic approaches on how schools should promote multilingualism. This study, therefore, looked at how Ubuntu translanguaging can be applied as a systematic approach in schools to promote multilingualism. This small-scale exploratory qualitative study made use of semi-structured interviews and classroom observations to explore how teachers incorporated and understood the Policy in promoting multilingualism. It was found that teachers used more than one language to enhance learning, though they believed this was not allowed and that they were required/expected to use only one language for learning and teaching at a time. The study concludes that there is a misunderstanding or misinterpretation of the Policy and recommends that the policy be unpacked and clarified for teachers. It further recommends the Ubuntu translanguaging pedagogy to be accepted as a systematic approach to promote multilingualism.